The Education and History of Timur Lenk from Uzbekistan - Ruzmetov Mirzabek (Indonesian Journal of Educational Research and Technology, 2023)
This paper briefly examines Timur Lenk, a great Muslim conqueror from Uzbekistan, from an educational perspective. This paper is crucial for educating our generation, particularly the Muslim generation that includes prominent Muslims with broad perspectives who have conquered the world. For Muslim countries to improve their socioeconomic standing, this paper is intended to advance their spirit. At the moment, these countries still have limited socioeconomic conditions.